PENGARUH PEMBERIAN SUSU KEDELAI (GLICINE MAX L. MERR) TERHADAP KADAR ASAM URAT PADA IBU - IBU MENOPAUSE DI PENGAJIAN AISYIYAH - REZA FAHLEVI Y.P; ROBITAH ASFUR (JURNAL ILMIAH KOHESI, 2020)
Women generally experience hyperuricemia during menopause because it is associated with a decrease in estrogenproduction. The presence of estrogen is very important to help regulate uric acid secretion so that it can protect women fromhyperuricemia. Isoflavones, including flavonoids, are often found in legumes, one of which is soybeans. Generally,isoflavones are found in soybeans and their processed products in the form of glycosides, which are inactive forms ofisoflavones. Flavonoids can contribute to reducing oxidative levels through inhibition of related enzymes, including inhibitionof xanthine oxidase action. This study aims to determine the effect of giving soy milk (Glycine max (L.) Merr.) on blood uricacid levels in menopausal women at Pengajian Aisyiyah. This study was experimental design of one group pretest and posttest with a sample of 40 menopausal women taken by total sampling. This study was conducted for 3 months andmeasurement of uric acid levels before and after administration of soy milk using a measurement of peripheral uric acidlevels. The results were analyzed using SPSS. Of the 30 subjects who met the inclusion and exclusion criteria, the averagevalue of uric acid pretest = 5.98 mg/dl and the average value of posttest uric acid = 5.51 mg/dl. There is a difference betweenthe value of the uric acid level pretest and posttest = 0.46 mg/dl. There is an effect of giving soy milk to uric acid levels withp=0.02.